STRATEGI PEMBELAJARAN BERBASIS PEMBENTUKAN KRAKTER PESERTA DIDIK PADA MADRASAH IBTIDAIYAH - Idhar Idhar (Prodi PAI STIT Sunan Giri Bima, 2022)
A teacher's learning strategy, namely tricks, tactics and planning to achieve learning goals effectively. From this sentence it can be understood that learning that is regulated by a planned and systematic strategy will lead students to be free in accepting the learning process. as well as the characteristics of the students. Therefore, the strategy is one way in the effective learning process that is owned by a teacher in achieving educational goals. The learning strategy of a teacher in shaping the character of students can actually be seen how a teacher is able to build principles in learning. So the principle is how a teacher motivates students about the meaning and benefits of learning because learning is actually a step or process of helping students become a generation that can be relied upon for survival for the future. So if students are correct with a planned strategy then it is likely that they will be aware of the information obtained and if students understand it will certainly affect their behavior and character.